Anti-5′-Nucleotidases (5′-ND) and Acetylcholinesterase (AChE) Activities of Medicinal Plants to Combat Echis carinatus Venom-Induced Toxicities. (4th February 2021) - Aslam, Nazia; Fatima, Syeda; Khalid, Sofia; Hussain, Shahzad; Qayum, Mughal; Afzal, Khurram; Asad, Muhammad Hassham Hassan Bin
Abstract : Echis carinatus is one of the highly venomous snakes of Pakistan that is responsible for numerous cases of envenomation and deaths. In Pakistan, medicinal plants are commonly used traditionally for snakebite treatment because of their low cost and easy availability in comparison with antivenom. The current research is aimed at evaluating the inhibitory activity of Pakistani medicinal plants against acetylcholinesterase and 5 ′ -nucleotidases present in Echis carinatus venom. Acetylcholinesterase and 5 ′ -nucleotidase enzymatic assays were performed at different venom concentrations to check the activity of these enzymes. Methanolic extracts from different parts of plants were used for in vitro determination of their inhibitory activity against 5 ′ -nucleotidases in snake venom. Active methanolic extracts were subsequently fractioned using different solvents, and these fractions were also assessed for their anti-5 ′ -nucleotidase activity. Results of this study exhibited that Eugenia jambolana Willd. ex O. Berg, Rubia cordifolia L., Trichodesma indicum (L.) R. Br., Calotropis procera (Wild.) R. Br., Curcuma longa L., and Fagonia arabica L. were able to significantly (p > 0.5 ) neutralize the 5 ′ -nucleotidase activity by 88%, 86%, 86%, 85%, 83.7%, and 83%, respectively, compared with a standard antidote (snake venom antiserum). Thus, this study indicates that these plants possess the potential to neutralize one of the toxic enzymatic components of Echis carinatus venom and hence can help to augment the future efforts of developing alternative therapy for the management of snakebites.